Answer: [OH-] = 1.8 x 10^-7 Explanation: pH + pOH = 14 –> 6.93 + pOH = 14 *subtract 6.93 from both sides pOH = 7.07 –> 10^pH => 10^-6.93 => 1e – 6.93 [H+] –> H+ x OH- = 1 x 10^-6.93 *divide H+ from both sides –> [OH-] = 1.17 x 10^-7 or 1.8 x 10^-7 Log in to Reply

Answer:[OH-] = 1.8 x 10^-7

Explanation:pH + pOH = 14 –> 6.93 + pOH = 14 *subtract 6.93 from both sides

pOH = 7.07

–>

10^pH => 10^-6.93 => 1e – 6.93 [H+]

–>

H+ x OH- = 1 x 10^-6.93 *divide H+ from both sides

–>

[OH-] = 1.17 x 10^-7 or 1.8 x 10^-7